Upwelling Increases Net Primary Production of Corals and Reef-Wide Gross Primary Production Along the Pacific Coast of Costa Rica - Stuhldreier, Ines (2015)
https://www.frontiersin.org/articles/10.3389/fmars.2015.00113/full